Wartime evacuation and mortality from childhood leukaemia in England and Wales in 1945-9. - Kinlen, L; John, S (1994)
OBJECTIVE: To discover whether the wartime government evacuation of children from London and other population centres to rural districts was associated with any increase in childhood leukaemia. DESIGN: Observational study of mortality from leukaemia among the childhood population of England and Wales in relation to the unique population movements during the second world war. The 476 rural districts of England and Wales were ranked according to the ratio of government evacuees (two thirds of them children) to local children in September 1941. The districts were divided into three categories, each with similar numbers of children in 1947 but with different ratios of evacuees to local children ("low," "intermediate," "high"). Mortality from childhood leukaemia was examined in these three rural categories in 1945-9. Urban areas were also examined according to their exposure to evacuees. SETTING: Local authority areas of England and Wales. SUBJECTS: Children aged under 15. RESULTS: 47% excess of leukaemia at ages 0-14 years occurred in 1945-9 in the rural "high" category for evacuees relative to the "low" category, with a significant trend across the three categories. There were increases in both the 0-4 and 5-14 year age groups, but these were larger in the older age group. Rates 25% lower than average occurred in rural areas with few evacuees. CONCLUSION: These findings suggest that wartime evacuation increased the incidence of childhood leukaemia in rural areas and that other forms of population mixing may have contributed to the increases in past decades. Overall, they add to the appreciable evidence for an infective basis in childhood leukaemia.